2013
DOI: 10.4154/gc.2013.05
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual model for groundwater status and risk assessment - case study of the Zagreb aquifer system

Abstract: This paper presents a conceptual model of the Zagreb aquifer system. The conceptual model can be applied to groundwater status risk assesstnent and pollution risk assessment at the local seale, thus satisfying both environmental and preventative/limitation objectives of the Water Framework Directive (WFD) and Groundwater Directive (GWD). Its main purpose is to apply a risk assessment procedure, according to the WFD requirements, and to serve as a foundation for setting up a numerical model of flow in both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 21 publications
4
48
0
Order By: Relevance
“…The geographical position of the city of Zagreb between the south-west slopes of Mount Medvednica and the banks of the Sava River as well as the geological and pedological traits of the Zagreb aquifer system have been described in detail by Nakić et al (2013) who developed a conceptual model for groundwater status and pollution risk assessment at a local scale. The system, which is an alluvial unconfined aquifer, includes the city of Zagreb and its surroundings covering an area of 350 km 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The geographical position of the city of Zagreb between the south-west slopes of Mount Medvednica and the banks of the Sava River as well as the geological and pedological traits of the Zagreb aquifer system have been described in detail by Nakić et al (2013) who developed a conceptual model for groundwater status and pollution risk assessment at a local scale. The system, which is an alluvial unconfined aquifer, includes the city of Zagreb and its surroundings covering an area of 350 km 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Highly variable lithology, pedological features and land use characterize the broader region. The study area consists of a large alluvial plain that has two marked geomorphological features: the raised sealed terrace of the Sava River (varying in width down the rivers length), and a Holocene terrace (Nakić et al, 2013). Numerous meanders of the Sava River inundated fluvial cones and numerous bowl-shaped depressions abound in the alluvial plain.…”
Section: Locationmentioning
confidence: 99%
“…4 based on the operational monitoring data. Previous research has shown that nitrates present one of the main groups of contaminants in the Zagreb aquifer [5]. Furthermore, two areas with elevated nitrate concentrations have been observed, while lower concentrations generally appear in the vicinity of the Sava River and in the eastern part of the aquifer [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…Due to the expansion of the City of Zagreb and nearby rural areas, anthropogenic influence on groundwater quality has been observed, while nitrates have been recognized as one of the main contaminants [5]. Two main areas with elevated nitrate concentrations have been identified, one on the left bank of the Sava River, in a predominantly urban area, and the other on the right bank of the Sava River, in a predominantly agricultural area.…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation